Twelfth night - Dickins, Rosie; Unzner-Fischer, Christa Shakespeare, William (Usborne London, 2014)
When Viola is left shipwrecked on the coast of Illyria, she must disguise herself as a boy for protection. But when she becomes a page for Duke Orsino, things start to get a little complicated.